A Generalization of Contraction Principle on Partial Metric Spaces - Dhanokar, G.A.; Salunke, J.N. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
In this paper we have proved fixed point theorem using continuous and monotonically non-decreasing mapping ∅, Ψ: [ 0, ∞) -> [ 0, ∞) with ∅ (0) , Ψ (0) = 0.